Hubungan Pola Konsumsi Kopi dengan Kejadian Gastritis: The Relationship between Coffee Consumption Patterns and the Incidence of Gastritis - Latifa Tussa’adah; Feri Catur Yuliani; Rizal Fajri (Jurnal Keperawatan Berbudaya Sehat, 2026)
Gastritis is one of the most common gastrointestinal diseases found in healthcare facilities. Globally, the prevalence of gastritis reaches more than 50% of the world's population, while in Indonesia, the incidence remains high and is a major cause of outpatient visits. Coffee consumption patterns are suspected to be a risk factor for gastritis due to caffeine content, which can increase gastric acid secretion and irritate the gastric mucosa. This study aimed to determine the relationship between coffee consumption patterns and the incidence of gastritis in patients at Nurussyifa General Hospital, Kudus. This research used a quantitative approach with a correlational analytic design and a cross-sectional study method. A sample of 36 patients diagnosed with gastritis was selected using a total sampling technique. Coffee consumption patterns were measured using a questionnaire, while the incidence of gastritis was classified into acute and chronic gastritis based on medical diagnosis. Data were analyzed using the Spearman's Rho test. The results showed that most respondents had a low coffee consumption pattern (44.8%) and experienced acute gastritis (66.7%). The Spearman's Rho test revealed a p-value = 0.001 (p < 0.05), indicating a significant relationship between coffee consumption and the incidence of gastritis. In conclusion, there is a significant relationship between coffee consumption patterns and the incidence of gastritis in patients at Nurussyifa General Hospital, Kudus.